Analysis of sequential beach volleyball actions - Koch, C.; Tilp, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In recent years experts have criticized the analysis of single actions in sports games (Carling et al., 2005). Simple tally counts of observed single actions do not represent the process of sport games sufficiently. The missing consideration of game interactions leads to information out of context which limits useful conclusions for practitioners. Therefore, the aim of this study was to analyse the action sequences in beach volleyball by using a database with single action descriptions and subsequent specific database queries. Deduced from sports practice the following questions were of interest: How does the service technique affect the reception performance? How does the setting quality affect the attack performance? Do men and women perform similar? Methods The basis of action sequence analysis is a systematic notational analysis of single actions out of video recordings. The behaviour of male and female world league players (29 matches during a world tour tournament) was described and registered with the game analysis software "Statshot" concerning technique, quality, location of action, direction and type of movement (Tilp et al., 2006). During the analysis the collected actions (approx. 16000) were classified regarding their affiliation to rallies and their temporal position during the rallies. Subsequently, database queries allowed the analysis of actions sequences. Chi-square tests were used to test statistical significance (p<0.05). Results The relationship between service technique and reception performance was observed to be gender specific. Female athletes received 44% of all float serves without a jump in poor (low ball trajectory or imprecise) or bad (mistake) quality (men: 30%). In contrast, 39% of all jump serves received by male athletes were of weak quality (women: 37%). Gender differences could also be detected in the relationship between setting quality and attacking technique. While men and women used the same distribution of the two attacking techniques (smash and shot) following excellent and poor setting actions, a different behaviour could be observed following setting actions of medium quality. While women played much more shots (72%) than smashes (28%), men used both techniques equally. All mentioned differences were statistically significant. Discussion The presented and additional results indicate that the analysis of sequential beach volleyball actions allows more specific conclusions in the game context than the analysis of single actions. It is possible to gain new and useful results for structure- and team analysis. Further research should reveal if stereotypic behaviour of teams can be identified with this method.